Evaluation of Services and Responses to Sexual Violence Cases in Higher Education: A Systematic Review - Rahmayani, Dwi; Rusli, A.M; Syamsu, Suhardiman (Journal of Public Administration and Government, 2024)
Sexual violence in higher education institutions is a global issue requiring effective services and response mechanisms to protect victims and ensure accountability. This systematic review aims to evaluate policies, victim support services, reporting mechanisms, and the effectiveness of institutional responses in addressing sexual violence cases. Using a systematic literature review (SLR) approach on articles published between 2018 and 2023, the review identifies gaps in implementation, inconsistent support systems, and a lack of survivor-centered approaches. This study highlights the need for strategic measures to improve institutional responses, ensure victim protection, and foster a safe and inclusive campus environment.